SOCIAL-ECONOMIC CONDITIONS AND HEALTH SELF-ASSESSMENT IN LATVIA – IS THERE ANY RELATIONSHIP? - Arturas Gataulinas; Marta Bancevica (European Scientific Journal, ESJ, 2015)
This article presents analysis of subjective health of Latvian population in the context of their social-economic life conditions. The results show that despite age, people’s social-economic living conditions play significant role in evaluations of their health situation. The current social economic circumstances tend to be positively related to subjective health evaluations. People who live in better social economic circumstances tend to evaluate their health better than people, who‘s social economic circumstances are worse. Social economic circumstances are described by net earnings, household‘s average income, education level and purchasing preferences. In total age and social economic circumstances factors explain about 40 % of variation in subjective health. This interrelationship could be viewed in that way, that inequality in people’s living conditions can reproduce inequality in evaluation of their health. As well it is possible to look at the problem from the completely different angle – inequality in health influence social-economic living conditions. Both of them could indicate the inequality problem possibilities.